The value of feedlot lighting - Smith, E.F.; Robertson, K.E.; Lipper, R.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The favorable results of previous tests of the value of beef feedlot lighting justified further studies. Faster and more efficient gains were obtained under lighted conditions in two years of farm testing.
Keywords: Beef; Feedlot; Lighting; Gain